1974
DOI: 10.1073/pnas.71.12.4986
|View full text |Cite
|
Sign up to set email alerts
|

Thiostrepton Inhibition of Initiation Factor 1 Activity in Polypeptide Chain Initiation in Escherichia coli

Abstract: Thiostrepton, a peptide antibiotic, inhibits the GTP-dependent 70S initiation complex formation (as measured by binding of fMet-tRNA to ribosomes and concomitant hydrolysis of GTP) only when initiation factor 1 is present to permit catalytic recycling of initiation factor 2 in the initiation reaction. When initiation factor 1 is absent, the binding of fMet-tRNA and GTP hydrolysis occur stoichiometrically with respect to initiation factor 2, and thiostrepton has no effect on either reaction under these conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1975
1975
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Let us now consider the kinetic behavior in the 30S system and the AcPhe-tRNA, poIy(U), 70S system. When 50S subunits are added to a 30S subunit initiation reaction mixture containing thermorubin, the equilibria can in principle be displaced in two directions: (a) by the normal formation of 70 S-fMet-tRNA-poly(A,U,G)-[GTP,IF] [see, e.g., Sarkar et al (1974)] followed by the translocation-like formation of the P-site complex via GTP hydrolysis and loss of IF; (b) by association of free 30S and 50S subunits into 70S ribosomes and sequestration as 70S-Tr and 70S-Tr-IFX-Q complexes. The first reaction in (b) would take less than 1 s at our concentrations (Wishnia et al, 1975); even the presence of 30S-IF-3 complexes would not raise the apparent half-time of formation of 70S particles to more than ~20-30 s (Chaires et al, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…Let us now consider the kinetic behavior in the 30S system and the AcPhe-tRNA, poIy(U), 70S system. When 50S subunits are added to a 30S subunit initiation reaction mixture containing thermorubin, the equilibria can in principle be displaced in two directions: (a) by the normal formation of 70 S-fMet-tRNA-poly(A,U,G)-[GTP,IF] [see, e.g., Sarkar et al (1974)] followed by the translocation-like formation of the P-site complex via GTP hydrolysis and loss of IF; (b) by association of free 30S and 50S subunits into 70S ribosomes and sequestration as 70S-Tr and 70S-Tr-IFX-Q complexes. The first reaction in (b) would take less than 1 s at our concentrations (Wishnia et al, 1975); even the presence of 30S-IF-3 complexes would not raise the apparent half-time of formation of 70S particles to more than ~20-30 s (Chaires et al, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…23,25 If this model were true, the dissociation of IF2 from the 70 S initiation complex would automatically leave the initiator fMet-tRNA in the ribosomal P-site, leaving space for the binding of the EF-Tu -GTPaminoacyl-tRNA ternary complex in the A-site, which would temporally follow the dissociation of IF2. However, several data and theoretical considerations clash with this simple and attractive model.…”
Section: Topographical Localization Of If2mentioning
confidence: 97%
“…In contrast, thiopeptides with 26-membered macrocycles (e.g., thiostrepton, siomycin, nosiheptide, berninamycin, and thiocillin/micrococcin) target the 50S subunit of by interacting with the 23S rRNA and ribosomal protein L11. ,, Binding is mediated primarily by interaction with 23S rRNA and is cooperative with L11. Resistance to thiopeptides of this variety occurs through mutation of either 23S rRNA or L11. , Alternatively, methylation of the 23S rRNA also confers resistance. Improving initial models, , more recent structural studies based on NMR, X-ray crystallography, and molecular modeling showed that these 26-membered thiopeptides bind to a cleft between the 23S rRNA and L11, , but covalent capture data suggest binding may be more on the surface of the rRNA and not between 23S/L11 . The interface of the 23S rRNA and L11 is called the “GTPase-associated center” and is crucial for ribosome function given its interaction with many translation factors. Consequently, the binding of thiopeptides with a 26-member macrocycle in this area can affect all phases of translation, but the most studied effects are on EF-Tu and EF-G during elongation. Inhibition of EF-Tu and tRNA delivery presumab...…”
Section: Thiopeptidesmentioning
confidence: 99%